Effectiveness of Insulin plant in Management of Diabetes Mellitus - Yonis Ismed (HM Publisher, 2021)
Diabetes mellitus, to this day, is still one of significant health problems and created significant morbidity and mortalityamong world populations. Current diabetic drugs still have unpleasant side effects and costly price. Seeking new diabetic drugs from natural resources is one of the practical action for alternative management of the disease. Insulin plant, originated from Andes, has been cultivated in Indonesia. Insulin plant is rich in caffeic acid, clorgenic acid, flavonoid, fenolic compound and sesquiterpenic lactone has antihyperglycemic and antioxidant effect that possibly have a role in diabetes management. Several studies have reported potential of insulin plant as antidiabetic agent. This review aims to summarize and organize current literature on effectiveness and role of insulin plant on diabetes mellitus patient